Alterações morfológicas e patológicas em esqueletos de boto-cinza Sotalia fluviatilis (Gervais, 1853) do litoral do Estado do Rio de Janeiro - Fragoso, Ana Bernadete Lima (2001)
Sotalia fluviatilis (Gervais, 1853) (Mammalia, Cetacea, Delphinidae), the tucuxi dolphin, is the most common delphinid on Rio de Janeiro coast. However, osteological information about this species are very limited. To increase the knowledge about bony changes in skeletals of this species, a study was realized on 75 specimens. The material consisted of skeletals remains stored in institutional collections that resulted from strandings and incidental caught on fisheries along the coast of Rio de Janeiro. This research had the objective of identify the bony changes and relate its frequency considering sex, age, size, physical maturity, presence by vertebral column region and individual localities. The bones were measured and examined to identify the presence, localization and development degrees of morphological and pathological changes. The lesions was distinguished in traumatic, degenerative, infectious and developmental categories. Most of specimens (77,3%) had some bone lesion sort of traumatic (n=47), degenerative (n=25), infectious (n=24) or developmental (n= 22) origin. A reduced number of specimens (n=4) had all lesion categories. The number of affected bones reach one to twenty-five, although the most of specimens (50,7%) had six to ten bones with lesions. The most affected regions of vertebral column was the cervical and thoracic. ln general, the number of lesions and the affected bones had tendency to increase with aging of specimens and was related with the individual size too. The number of affected bones was similar between sex. Individuals from central area of Rio de Janeiro state had more incidence of lesions and bone affected by changes. The study of bony changes is a important tool for access pathological information on specimens that the necropsy is not possible. The frequency of occurrence of morphological and pathological changes in this species could be associated to particularities from region, the form of natural resources use and other interference occasioned by human activity.